Enhancement of the anticancer effect of atorvastatin-loaded nanoemulsions by improving oral absorption via multivalent intestinal transporter-targeting lipids - Laxman Subedi; Prashant Pandey; Bikram Khadka; Jung-Hyun Shim; Seung-Sik Cho; Seho Kweon; Youngro Byun; Ki-Taek Kim; Jin Woo Park (Taylor & Francis Group, 2022)
Atorvastatin (ATV) has attracted considerable attention as a potential therapeutic agent for cancer because it inhibits cancer cell proliferation by suppressing the mevalonate pathway. However, because of its low oral absorption, high doses of ATV are required for chemotherapeutic applications. In this study, we constructed ATV-loaded nanoemulsions (ATV-NEs) containing multivalent intestinal transporter-targeting lipids to improve the oral bioavailability of ATV. ATV-NEs were prepared via oil-in-water emulsification for transporter-targeted delivery, and contained the following anchors: an ionic complex of deoxycholic acid (DOCA) with the cationic lipid 1,2-dioleyl-3-trimethylammonium propane (DOTAP) (DOCA-DOTAP), a biotin-conjugated lipid (Biotinyl PE), and d-alpha-tocopherol polyethylene glycol succinate (TPGS) to allow bile acid- and multivitamin transporter-mediated permeation of ATV without P-glycoprotein (P-gp)-mediated efflux. The optimized formulation (ATV-NE#6) had 1,091% higher oral bioavailability than free ATV. Finally, treatment of 4T1 cell-bearing mice with oral ATV-NE#6 (equivalent to 40 mg/kg ATV) significantly suppressed tumor growth; the maximum tumor growth reduction was 2.44-fold that of the control group. The results thus suggest that ATV-NEs allow for effective oral chemotherapy by enhancing the oral bioavailability of ATV.